Silicone oil adhesion to hydrophobic acrylic intraocular lenses: a comparative laboratory study of a new versus an established hydrophobic acrylic intraocular lens material - Auffarth, Gerd U.; Fang, Hui; Wang, Qiang; Hengerer, Fritz; Khoramnia, Ramin; Son, Hyeck Soo; Schickhardt, Sonja (Journal of ophthalmology, 2021)
Background. In vitro assessment of silicone oil adhesion to a new hydrophobic acrylic intraocular lens (IOL) material, the Clareon model CNA0T0, compared with the established AcrySof model SN60WF was carried out. Methods. Silicone oil adhesion was assessed for two types of IOLs, Clareon CNA0T0 (n = 10) and AcrySof SN60WF (n = 10). Lenses were immersed in an aqueous sodium chloride solution for 12 hours and then incubated at room temperature in silicone oil for 12 hours. The lenses were washed with distilled water and photographed at 25x magnification using a microscope. The percent coverage was calculated by dividing the area of oil coverage by the total surface area of the lens. Results. Silicone oil adhesion to the surface of the CNA0T0 lens ranged from 4% to 22%, with a mean ± SD coverage of 8% ± 4%. Silicone oil adhesion to the surface of the SN60WF lens ranged from 1% to 17%, with a mean coverage of 9% ± 4%. The silicone oil adhesion of CNA0T0 was equivalent to that of SN60WF (). Conclusions. The new Clareon model CNA0T0 IOL has silicone oil adhesion and interaction that are equivalent to the established AcrySof IOL.
Gesehen am 22.12.2021